Prevention of the Construction of Childfree Behavior in the Community: Study of Takhrij and Syarah Hadith - Azra, Lazuardy; Alkhair, Muhammad Zia (Journal of Takhrij Al-Hadith, 2022)
This study aims to discuss the hadith about childfree. This study uses a qualitative approach by applying the descriptive-analytical method. The formal object of this research is the science of hadith, while the material object is the hadith about childfree in Nasa'i history No. 3175. The results and discussion of this study indicate that the status of quality hadith hasan li ghairihi that meets the qualifications of maqbul ma'mul bih for the practice of Islam. This study concludes that the hadith narrated by Nasa'i No. 3175 is relevant to be used as motivationin preventing childfree thinking in society.